The Influence of Exposure to Going Seventeen Content on Teenagers’ Digital Communication Patterns - Karenina Jasmine; Mulyono M; David Rizar Nugroho; Enden Darjatul Ulya (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of exposure to Going Seventeen content on teenagers’ digital communication patterns. The research employed a quantitative method with a descriptive quantitative approach. Data were collected through questionnaires and processed using SPSS and Microsoft Excel. The findings indicate a positive relationship between the level of exposure to Going Seventeen content and teenagers’ digital communication patterns. The higher the exposure, the stronger its influence on how teenagers interact in digital spaces. Going Seventeen functions not only as entertainment but also as a medium that shapes communication styles, self-expression, and social identity within online fan communities. The study also reveals that the level of exposure to Going Seventeen content falls into the very high category, with an average score of 4.29. This suggests that teenagers have a high level of engagement with the show in terms of frequency, duration, and attention. Overall, Going Seventeen has become a highly favored form of digital consumption and an integral part of teenagers’ online routines.